Effect of melt sonocrystallization on pharmacotechnical properties of paracetamol, indomethacin and mefenamic acid characterized by dynamic laser scattering and its impact on solubility. (May 2013) - Kumar, Brijesh; Sharma, Vijay; Pathak, Kamla
<x xml:space="preserve">Abstract</x> The purpose of the research was to employ a novel particle engineering technique-melt sonocrystallization (MSC) for some nonsteroidal anti-inflammatory drugs for development of more soluble forms of the drugs without the use of excipients. The original forms of Paracetamol (OFPCM), Indomethacin (OFIMC) and Mefenamic acid (OFMA) were subjected to MSC to improve physicochemical properties. MSC forms of PCM, IMC and MA were subjected to dynamic laser scattering for particle size analysis to quantize mean particle size, specific surface area, interquartile coefficient of skewness, kurtosis and span. Rheological and solubility analysis, X-ray powder diffraction and scanning electron microscopy were conducted for validating the effect of MSC on powder particles. On melt sonocrystallized form of drug powders exhibited improved micromeritic properties, the mean particle size was reduced while the specific surface area increased effectively. Frequency distribution curves showed reduction in asymmetry and skewness that was confirmed by interquartile coefficient of skewness values. Equilibrium solubility of MSC form of PCM, IMC and MA was higher than the original forms. Similarly the intrinsic dissolution rate was approximately 1.5 times higher in comparison to original form of drugs. X-ray powder diffraction shows decreased relative intensities of peaks of MSC forms due to reduction in the crystallinity that was confirmed by visualization of MSC particles by scanning electron microscopy. Conclusively, MSC is a promising cost-effective technique that may afford powder with improved flow and formulative properties as well as improved solubility and dissolution.